Design and characterization of dietary assessment in the German National Cohort - Knüppel, Sven; Clemens, Matthias; Conrad, Johanna; Gastell, Sylvia; Michels, Karin; Leitzmann, Michael; Krist, Lilian; Pischon, Tobias; Krause, Gerard; Ahrens, Wolfgang; Ebert, Nina; Jöckel, Karl-Heinz; et al. (European journal of clinical nutrition, 2019)
The aim of the study was to describe a novel dietary assessment strategy based on two instruments complemented by information from an external population applied to estimate usual food intake in the large-scale multicenter German National Cohort (GNC). As proof of concept, we applied the assessment strategy to data from a pretest study (2012-2013) to assess the feasibility of the novel assessment strategy. First, the consumption probability for each individual was modeled using three 24 h food lists (24h-FLs) and frequencies from one food frequency questionnaire (FFQ). Second, daily consumed food amounts were estimated from the representative German National Nutrition Survey II (NVS II) taking the characteristics of the participants into account. Usual food intake was estimated using the product of consumption probability and amounts. We estimated usual intake of 41 food groups in 318 men and 377 women. The participation proportion was 100, 84.4, and 68.5% for the first, second, and third 24h-FL, respectively. We observed no associations between the probability of participating and lifestyle factors. The estimated distributions of usual food intakes were plausible and total energy was estimated to be 2707 kcal/day for men and 2103 kcal/day for women. The estimated consumption frequencies did not differ substantially between men and women with only few exceptions. The differences in energy intake between men and women were mostly due to differences in estimated daily amounts. The combination of repeated 24h-FLs, a FFQ, and consumption-day amounts from a reference population represents a user-friendly dietary assessment approach having generated plausible, but not yet validated, food intake values in the pretest study.
Gesehen am 09.12.2019